Genome Size Variation Assessment in Vitis vinifera L. Landraces in Ibiza and Formentera (Balearic Islands) - Raquel González; Joan Vallès; Teresa Garnatje (Plants, 2022)
Plant genome size has many applications in different biological fields including ecology and plant breeding. The 2C value for Vitis vinifera L. has not been widely studied; furthermore, to date, no data from local landraces in the Pityusic Islands (the two smaller inhabited Balearic Islands, Ibiza, and Formentera) have been reported. This research aims to contribute to this knowledge and investigate whether there are variations between different grape landraces cultivated in Ibiza and Formentera and also among the same landraces on each island. To this end, 36 accessions of 15 cultivars and 6 landraces, identified with SSR markers, were assessed using flow cytometry. The results revealed that 2C values ranged from 1.09 pg to 1.28 pg. There were statistically significant differences in ‘AG1’ and ‘AG2’ landraces and ‘Santa Magdalena’, ‘Garnatxa’, ‘Danugue’, and ‘Valencí tinto/Grumier’ cultivars. No statistically significant differences were found in terms of the genome size content between islands. Statistically significant differences were found in accessions within ‘AG2’ landrace group and ‘Beba’ cultivar. The results presented here constitute the first-ever reported information on genome size in the genus Vitis vinifera in Pityusic, Balearic, and, in general, Spanish accessions, and they are one of the largest prospections in this field for this species anywhere. Further research should be conducted to explain the differences in nuclear DNA content found between landraces and cultivars studied here with others cultivated in different islands or countries to understand whether genome size varies in modern cultivars compared with local landraces. Additionally, it would be interesting to investigate whether there is a relationship between genome size and adaptations to diverse climatology conditions, crop management, and ripening characteristics.